2020
DOI: 10.3389/fcell.2020.00730
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-4–/– Mice Have Smaller Muscle Fibers, Increased Akt/mTOR/S6K1 and Notch/HES-1 Pathways, and Alterations in Extracellular Matrix Components

Abstract: Background: Extracellular matrix (ECM) remodeling is essential for skeletal muscle development and adaption in response to environmental cues such as exercise and injury. The cell surface proteoglycan syndecan-4 has been reported to be essential for muscle differentiation, but few molecular mechanisms are known. Syndecan-4 −/− mice are unable to regenerate damaged muscle, and display deficient satellite cell activation, proliferation, and differentiation. A reduced myofiber basal lamina has also been reported … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 57 publications
(89 reference statements)
4
26
0
Order By: Relevance
“…38 Encoding actinins, cadherins and calcium channel subunits, which are molecules involved in cell-matrix and cell-cell adhesions, and are therefore likely to interact functionally with SDC4. 44,45 In this study we demonstrated that SDC4 has a high predictive ability for NAFLD.…”
Section: Discussionsupporting
confidence: 51%
“…38 Encoding actinins, cadherins and calcium channel subunits, which are molecules involved in cell-matrix and cell-cell adhesions, and are therefore likely to interact functionally with SDC4. 44,45 In this study we demonstrated that SDC4 has a high predictive ability for NAFLD.…”
Section: Discussionsupporting
confidence: 51%
“…They described that the absence of syndecan-4 reduces the degree of barium chloride-induced muscle regeneration compared to that in the wild type. Comparing normal and syndecan-4 KO mice, Ronning et al revealed decreased MyoD and MyoG expression and smaller myotube cross-sectional area in syndecan-4 KO [ 36 , 54 ]. Importantly, during in vivo studies, the migratory ability of the cells also have high impact for the fusion events.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, during in vivo studies, the migratory ability of the cells also have high impact for the fusion events. Our previous results indicated that silencing syndecan-4 expression reduces the migration of mammalian myoblasts in vitro [ 26 , 27 ], which may explain the reduced regeneration and myotube formation in syndecan-4 KO mice [ 36 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting a central role of syndecan-4 in stress sensing via connections in the ECM, we recently observed that syndecan-4 ablation in skeletal muscle resulted in smaller muscle fibers, alterations in ECM components and an elevated Ser473-Akt phosphorylation (pSer473-Akt) ( Rønning et al, 2020 ). The upregulation of pSer473-Akt was accompanied by an increase in phosphorylation of downstream components of Akt signaling such as mTOR and RPS6 ( Rønning et al, 2020 ).…”
Section: Introductionmentioning
confidence: 88%